Regular ultrasonographic screening significantly prolongs patency of PTFE grafts - Malik, Jan; Slavikova, Marcela; Svobodova, Jaroslava; Tuka, Vladimir (Kidney international, 2005)
BACKGROUND: Polytetrafluoroethylene (PTFE) dialysis grafts have considerably shorter patency than native arteriovenous fistulas, despite the use of a complex of screening monitoring methods (venous pressure, access flow). PTFE grafts are used often in subjects with depleted subcutaneous veins after previous abandoned accesses, so keeping the access patent is crucial. We hypothesized that regular duplex Doppler ultrasound screening for access stenoses, together with their sooner treatment, would prolong PTFE graft patency. METHODS: We performed a randomized, prospective study of PTFE grafts' cumulative patency in 192 subjects. In group 1, regular ultrasound examinations performed every 3 months was added to traditional screening (i.e., regular access examination at hemodialysis unit, monitoring of venous pressure and access flow). Group 2 was screened only traditionally (without ultrasound). Interventions of suspected stenoses were indicated by nephrologists, vascular surgeon, and, in group 1, also by ultrasonography. Classic ultrasound criteria for significant stenosis were used, even if the access flow had not been decreased. The mean follow-up lasted 392 +/- 430 days. RESULTS: Groups were similar with respect to age, gender, diabetes status, and number of previous abandoned accesses. Group 1 had significantly longer access patency (P < 0.001). Number of interventions per graft was 2.1 +/- 1.8 and 1.3 +/- 1.0 in group 1 and group 2. CONCLUSIONS: Regular screening duplex Doppler ultrasonography results in significantly longer PTFE graft patency due to early detection of access stenosis and, thus, more frequent elective interventions of access stenoses.
Keywords: cévní protézy; diabetické nefropatie; Male; průchodnost cév; polytetrafluoroethylen; dialýza ledvin; mužské pohlaví; Vascular Patency; reprodukovatelnost výsledků; Reproducibility of Results; Blood Vessel Prosthesis; Renal Dialysis; arteriovenózní píštěl; Diabetic Nephropathies; lidé; Arteriovenous Fistula; ženské pohlaví; Polytetrafluoroethylene; Humans; Female; lidé středního věku; Middle Aged